A kind of polybutadiene latex and ABS resin and preparation method thereof

A polybutadiene latex with precise particle size and monomer content addresses the agglomeration issue in ABS resin electroplating, enhancing surface quality and yield by ensuring uniform dispersion and grafting.

CN116515026BActive Publication Date: 2024-12-17KINGFA SCI & TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310478613.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2024-12-17
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

Existing ABS resin materials suffer from high butadiene content leading to rubber agglomeration during electroplating, resulting in surface pitting defects, particularly in automotive parts, with yield rates below 50%.

Method used

A polybutadiene latex with controlled average particle size (290-315 nm) and narrow half-peak width (20-150 nm) distribution, along with a residual butadiene monomer content of 0.005%-1.6%, is used to prepare an ABS resin, ensuring uniform dispersion and grafting, thereby reducing pitting and improving coating adhesion.

Benefits of technology

The controlled polybutadiene latex enhances electroplating surface appearance and bonding strength, achieving a surface pitting grade of 3A-5A and coating adhesion of 0.62-1.28 kgf/cm, significantly improving yield and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004206318270000071
    Figure BDA0004206318270000071
  • Figure BDA0004206318270000081
    Figure BDA0004206318270000081
  • Figure BDA0004206318270000082
    Figure BDA0004206318270000082
Patent Text Reader

Abstract

The present invention relates to a polybutadiene latex and ABS resin and a preparation method thereof. The average particle size of the polybutadiene latex is 290-315 nm, and the half-peak width of the number average particle size distribution curve is 20-150 nm. The residual butadiene monomer content in the polybutadiene latex accounts for 0.005%-1.6% of the dry basis of the entire polybutadiene latex. The ABS resin comprises: 15-40 parts of ABS high-rubber powder and 60-78 parts of styrene-acrylonitrile copolymer. The ABS resin has good electroplating surface appearance and coating bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer technology, and particularly relates to a polybutadiene latex and ABS resin and a preparation method thereof. Background Art

[0002] Compared with metal parts, plastic electroplating parts can not only achieve good metal texture, but also significantly reduce the weight of parts. While effectively improving the appearance and decorativeness of plastic materials, it also improves its electrical, thermal and corrosion resistance performance, and at the same time improves the surface mechanical strength. However, the selection of plastic materials for electroplating must comprehensively consider factors such as material processing performance, mechanical properties, material cost, electroplating cost, difficulty of electroplating, and dimensional accuracy. Among many polymer materials, ABS resin materials have excellent comprehensive properties and are easy to process and shape due to their structural advantages. In addition, the ABS surface is easily corroded by the electroplating solution to obtain a higher coating bonding force. Therefore, it is currently widely used in electroplating. ABS resin specifically refers to a blend of a graft copolymer of polybutadiene rubber and monomers styrene and acrylonitrile with a matrix SAN resin, where A represents acrylonitrile, B represents butadiene, and S represents styrene. For electroplating grade ABS plastics, the content of each component of the material is critical, among which the content of butadiene has a greater impact on electroplating. This is because ABS is a non-conductor. To electroplate it, a conductive layer must be covered on the surface of the material. The formation of the conductive layer requires processes such as roughening, neutralization, sensitization, activation and chemical plating. Roughening is to etch away butadiene through oxidation reaction, and form an activated hydrophilic surface and anchor structure on the part to improve the bonding strength of the coating. Therefore, the higher the butadiene content, the better the adhesion of the coating. In the actual application process, in order to blindly improve the adhesion of the coating, material designers greatly increase the content of butadiene rubber and increase the particle size of butadiene rubber. This makes butadiene rubber very easy to agglomerate in ABS resin, and causes a large number of defects such as pitting on the surface of injection molded parts, which greatly reduces the yield rate of electroplated parts. Especially for automotive electroplating door handles, grilles, decorative strips and other interior and exterior parts that have very demanding usage requirements, defects such as pitting make the yield rate of electroplating products less than 50%, causing great trouble to automobile OEMs and parts suppliers.

[0003] Chinese patent CN114479300A discloses an electroplating grade ABS resin composition, which comprises, by weight, 15-30 parts of polybutadiene rubber grafted acrylonitrile and styrene copolymer, 60-80 parts of base SAN resin and 5-10 parts of extended SAN resin. The acrylonitrile content in the base SAN resin is 30-34wt%, and the acrylonitrile content in the extended SAN resin is 24-27wt%. By adding the extended SAN resin, the compatibility of the polybutadiene rubber in the base SAN resin is improved, so that the ABS forms a sharp-edged reverse shoe structure in the electroplating roughening stage, provides a greater coating tension, greatly reduces the formation of pitting defects, and improves the qualified rate of electroplated products. Chinese patent CN104045963B discloses a glass fiber reinforced high-gloss ABS resin composition suitable for electroplating. The patent adopts a low molecular weight SAN additive, which can not only enhance the rigidity of the ABS resin composition, but also effectively provide the fluidity of the ABS resin composition, reduce the exposure of glass fibers and make the surface of the injection molded parts present a higher gloss, which can effectively reduce the linear thermal expansion coefficient of plastic electroplated products, and effectively reduce the leakage of glass fibers and pitting caused by leakage. Chinese patent CN112489635A discloses a transparent PC / ABS alloy and its preparation method. The invention first mixes and extrude ABS resin and styrene-grafted butadiene rubber, and uses a compatibilizer to wrap the rubber phase in the ABS in the styrene phase to prevent the agglomeration of rubber. The two-step method first prepares a transparent ABS masterbatch with a refractive index close to PC, and then co-extrudes the masterbatch and PC resin to prepare a transparent PC / ABS alloy. The above technical scheme can reduce the possibility of pitting to a certain extent, but it is all from the level of rear-end modification, and the dispersion of rubber is forced by introducing a third component or a compatibilizer, which cannot fundamentally solve the thermodynamic tendency of rubber self-agglomeration. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a polybutadiene latex and ABS resin and a preparation method thereof, so as to overcome the defect that a large number of pits are easily generated during the electroplating process of ABS resin in the prior art.

[0005] The invention provides a polybutadiene latex, wherein the average particle size of the polybutadiene latex is 290-315nm, the half peak width of the number average particle size distribution curve is 20-150nm, and the residual butadiene monomer content in the polybutadiene latex accounts for 0.005%-1.6% of the dry basis of the entire polybutadiene latex.

[0006] The above-mentioned residual butadiene monomer content ratio is quantitatively obtained by gas chromatography according to the external standard method, specifically: 0.1-0.5g of the sample is weighed and constant to 0.1mg, and the headspace bottle containing the sample is placed in the headspace automatic sampler, and the gas chromatography of the non-polar chromatographic column (PC-1) of the gas chromatography is used, and the FID detector measures the gas chromatographic spectrum integral area of ​​the residual butadiene in the latex, and the amount of residual butadiene is obtained by converting the standard curve, and the value is divided by the total amount of the latex dry basis of the entire polybutadiene.

[0007] The average particle size of the polybutadiene latex in the present invention is 290-315 nm, which can be understood to include but not limited to 290 nm, 295 nm, 298 nm, 300 nm, 302 nm, 303 nm, 305 nm, 308 nm, 310 nm, 312 nm, and 315 nm.

[0008] The half-peak width of the number average particle size distribution curve in the present invention is 20-150nm, which can be understood as including but not limited to 20nm, 22nm, 25nm, 28nm, 30nm, 33nm, 35nm, 40nm, 42nm, 45nm, 50nm, 53nm, 55nm, 58nm, 60nm, 63nm, 65nm, 70nm, 72nm, 75nm, 78nm, 80nm, 83nm, 84nm, 86nm, 87nm, 88nm, 89nm, 90nm, 91nm, 92nm, 93nm, 94nm, 95nm, 96nm, 97nm, 98nm, 99nm, 100nm, 101nm, 102nm, 103nm, 104nm, 105nm, 106nm, 107nm, 108nm, 109nm, 110nm, 111nm, 112nm, 113nm, 114nm, 115nm, 116nm, 117nm, 118nm, 119nm, 120nm, 121nm 5nm, 88nm, 90nm, 92nm, 95nm, 98nm, 100nm, 103nm, 105nm, 107nm, 110nm, 113nm, 115nm, 117nm, 120nm, 123nm, 125nm, 128nm, 130nm, 133nm, 135nm, 138nm, 140nm, 142nm, 145nm, 148nm, 150nm.

[0009] The residual butadiene monomer content in the polybutadiene latex of the present invention is 0.005% to 0.1% of the dry basis of the entire polybutadiene latex.

[0010] 1.6% may be understood to include, but not limited to, 0.005%, 0.008%, 0.01%, 0.012%, 0.015%, 0.018%, 0.021%, 0.025%, 0.028%, 0.030%, 0.032%, 0.035%, 0.038%, 0.040%, 0.045%, 0.050%, 0.055%, 0.060%, 0.065%, 0.070%, 0.071%, 0.072%, 0.073%, 0.074%, 0.076%, 0.077%, 0.078%, 0.080%, 0.081%, 0.082%, 0.083%, 0.084%, 0.085%, 0.086%, 0.087%, 0.088%, 0.089%, 0.090%, 0.091%, 0.092%, 0.093%, 0.094%, 0.095%, 0.096%, 0.097%, 0.098%, 0.099%, 0.010%, 0.101%, 0.111%, 0.112%, 0.113%, 0.114%, 0.115%, 0.116%, 0.117%, 0.118%, 0.119%, 0.120%, 5%, 0.08%, 0.085%, 0.090%, 0.095%, 0.1%, 0.15%, 0.2%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1.0%, 1.2%, 1.3%, 1.5%, 1.6%.

[0011] Preferably, the average particle size of the polybutadiene latex is 300-310 nm, and the half-peak width of the number average particle size distribution curve is 30-100 nm.

[0012] Preferably, the residual butadiene monomer content in the polybutadiene latex accounts for 0.01%-0.8% of the dry basis of the entire polybutadiene latex.

[0013] Preferably, the weight fraction of the polybutadiene latex gel is 50-95%. The gel content is controlled within a reasonable range so that it can always maintain excellent dispersion performance during the subsequent polymerization and mixing process, and better avoid poor electroplating caused by rubber agglomeration. The test standard for gel content is "Determination of Gel Content of Synthetic Raw Rubber", standard number SH / T 1050-1991.

[0014] The present invention also provides a method for preparing polybutadiene latex, comprising:

[0015] The raw materials are mixed and polymerized to obtain polybutadiene latex, wherein the raw materials are calculated by weight as follows: 95-115 parts of butadiene, 0.02-6 parts of initiator, 0.02-10 parts of electrolyte, 0.1-12 parts of emulsifier, 0.01-6 parts of chain transfer agent, 0.02-8 parts of rubber particle size controller, 0-6 parts of gel content regulator, 40-400 parts of water, and the rubber particle size controller is polyoxyethylene carboxylate.

[0016] Preferably, the initiator includes one or more of sodium persulfate, potassium persulfate, ammonium persulfate, and azobisisobutylnitrile.

[0017] Preferably, the electrolyte includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate and potassium hydroxide.

[0018] Preferably, the emulsifier includes one or more of naphthalenesulfonic acid formaldehyde condensate sodium salt, naphthalenesulfonic acid formaldehyde condensate potassium salt, potassium oleate, potassium stearate, potassium disproportionated rosin acid, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfonate.

[0019] Preferably, the chain transfer agent includes one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, tetradecyl mercaptan, tridecyl mercaptan, undecyl mercaptan and decanyl mercaptan.

[0020] Preferably, the raw materials are calculated by weight as follows: 98-110 parts by weight of butadiene, 0.12-5 parts by weight of initiator, 0.05-6 parts by weight of electrolyte, 1-8 parts by weight of emulsifier, 0.1-4 parts by weight of chain transfer agent, 0.05-5 parts by weight of rubber particle size controller, 0.2-5 parts by weight of gel content regulator and 50-300 parts by weight of water.

[0021] Preferably, the rubber particle size control agent has the structural formula of RCOO (CH2CH2O) m H, wherein R is a long-chain alkyl group, the number of carbon atoms in the long-chain alkyl group is 4-19, and m is 4-11. More preferably, the number of carbon atoms in the long-chain alkyl group is 5-12, and m is 4-8.

[0022] Preferably, the gel content regulator is a dialkyl dithioxanthate, wherein the number of carbon atoms of the alkyl group is 1-13, and more preferably, the number of carbon atoms of the alkyl group is 1-10.

[0023] Preferably, the polymerization reaction is: heating to 55-85° C. and reacting for 23-38 hours.

[0024] The present invention also provides an ABS high-rubber powder, which is a copolymer of the above-mentioned polybutadiene latex, styrene and acrylonitrile.

[0025] Preferably, the weight fraction of the polybutadiene latex is 50-70%, and the weight fraction of acrylonitrile is 4-20%. More preferably, the weight fraction of the polybutadiene latex is 52-66%, and the weight fraction of acrylonitrile is 6-15%.

[0026] The present invention also provides an ABS resin, wherein the ABS resin components include, by weight: 15-40 parts of the above-mentioned ABS high-rubber powder and 60-78 parts of styrene-acrylonitrile copolymer.

[0027] The present invention also provides a method for preparing ABS resin, comprising:

[0028] The components are mixed, extruded through a twin-screw extruder, cooled, and pelletized to obtain ABS resin.

[0029] The present invention also provides an application of ABS resin in automobile interior and exterior electroplating parts, such as front and rear door handles, front grilles, interior trim strips, navigation panel frames, etc.

[0030] The average particle size of the polybutadiene latex of the present invention is controlled within the range of 290-315 nm, and the half-peak width of the number average particle size distribution curve is 20-150 nm. The extremely narrow particle size distribution makes the butadiene rubber in the latex present a nearly monodisperse characteristic, which is very different from the particle size distribution of the butadiene rubber obtained by polymerization by the traditional method. The closer to the average particle size, the more the number of rubber particles; the farther away from the average particle size, the number of rubber particles tends to zero. The butadiene latex with this characteristic has very excellent stability in the subsequent grafting and coagulation process, especially the grafting rate. The uniform grafting rate ensures that each butadiene rubber can be well grafted and coated, thereby avoiding agglomeration between rubbers and reducing the possibility of pitting of ABS resin during electroplating. The uniform dispersion of rubber helps to improve the bonding strength of the coating and avoid the occurrence of defects such as leakage plating. On the other hand, the residual butadiene monomer content in the polybutadiene latex accounts for 0.005%-1.6% of the dry basis of the entire polybutadiene latex. Since the residual butadiene monomer is very easy to react with the grafted monomers styrene and acrylonitrile, the appropriate residual butadiene monomer content can affect the proportion of butadiene units in the grafted chain segment in the grafted rubber, thereby improving the compatibility of the grafted rubber with the blended SAN resin, improving the dispersion of the rubber, and further reducing the possibility of appearance pitting of electroplated parts.

[0031] Beneficial Effects

[0032] The polybutadiene latex used in the present invention enables the ABS resin to have a better electroplating surface appearance and plating layer bonding strength.

[0033] The surface pitting grade of the ABS resin of the present invention is 3A-5A, and the coating adhesion is 0.62-1.28 kgf / cm. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0035] Source of reagents:

[0036] Butadiene: Industrial grade butadiene, purity greater than 96%, Huarui Chemical;

[0037] Initiator: potassium persulfate, commercially available;

[0038] Electrolyte: sodium bicarbonate, commercially available;

[0039] Emulsifier: sodium dodecylbenzene sulfonate, commercially available;

[0040] Chain transfer agent: n-dodecyl mercaptan, commercially available;

[0041] Rubber particle size control agent 1: polyoxyethylene hexanoate, C5H 11 COO(CH2CH2O)6H; American CIHEEM, LMEO-6; Rubber particle size control agent 2: polyoxyethylene laurate, C 11 H 23 COO(CH2CH2O)6H; American CIHEEM, LMEO-12; Rubber particle size control agent 3: polyoxyethylene stearate, C 17 H 35 COO(CH2CH2O)9H; LMEO-18 from CIHEEM, USA; Gel content regulator 1: dibutyl xanthate, CP8, Zhengzhou Aikem Chemical Co., Ltd.;

[0042] Gel content regulator 2: diisopropyl dithioxanthate, DIP, Shanghai Yuanye Biotechnology Co., Ltd.;

[0043] Gel content regulator 3: didodecyl dithioxanthate, DP, Hubei Xinkang Pharmaceutical Chemical Co., Ltd. Chemical Research Institute; Styrene: purchased from Aladdin Reagent Company, purity greater than or equal to 99%;

[0044] Acrylonitrile: purchased from Aladdin Reagent Company, purity greater than or equal to 99%;

[0045] Styrene-acrylonitrile copolymer: PN-118, Chi Mei, Taiwan;

[0046] Unless otherwise specified, a certain component (such as initiator, electrolyte) in the parallel embodiments and comparative examples of the present invention is the same commercially available product.

[0047] The preparation method of polybutadiene latex comprises:

[0048] According to the proportions in Table 1 and Table 2, the components were mixed, the temperature was raised to 55° C. to start the polymerization reaction, the temperature was continuously raised to 85° C. within 30 hours, and the reaction was completed after 32 hours to obtain polybutadiene latex.

[0049] Polybutadiene latex performance test:

[0050] (1) Particle size evaluation and particle size distribution test: Malvern laser diffraction particle size analyzer, model Mastersizer 3000E, was used to analyze the average particle size and particle size distribution of polybutadiene latex, and the number average particle size distribution curve was drawn and the half peak width was tested;

[0051] (2) Gel content (weight fraction) test: carried out in accordance with the test standard "Determination of gel content of synthetic raw rubber", standard number SH / T 1050-1991.

[0052] (3) Residual butadiene content: After drying, the latex is dissolved in a headspace bottle with N,N-dimethylformamide, heated to make the components to be tested reach gas-liquid equilibrium, and then quantitatively aspirate the headspace for gas chromatography determination. Qualitative analysis is performed based on retention time, and n-pentane is used as an internal standard for quantitative analysis by internal standard method. The peak at 2.25-2.50 min is the residual butadiene substance. A Shimadzu GC-MS-QP2010 gas chromatograph is used, and the chromatographic column is: RTX-WAX quartz capillary column, 30m×0.25mm×0.5μm; column temperature: 80℃ for 12min, 10℃ / min to 120℃ for 10min; injection port temperature: 220℃; detector temperature: 250℃.

[0053] ABS high-rubber powder: a copolymer of polybutadiene latex, styrene and acrylonitrile, and its preparation method is as follows: polybutadiene latex, styrene and acrylonitrile are mixed according to the ratio in Table 3, polybutadiene latex is added into a reactor, and 0.015 parts of ferrous sulfate is added into the reactor and stirred evenly, the reactor is heated to 67°C, and 2.51 parts of cumene hydroperoxide, acrylonitrile, styrene, 1.5 parts of tert-dodecyl mercaptan, 5 parts of sodium dodecyl sulfonate and 175 parts of deionized water are added, and the addition is continued dropwise for 2 hours. After heating is completed, the reaction is continued for 5 hours to obtain a grafted latex. 1000 parts of grafted latex were added to a coagulation reactor, stirring was started and heated to 75°C, 450 parts of 5% sulfuric acid were gradually added thereto, the addition was completed within 2 hours, and the temperature was raised to 91°C and maintained at the temperature for 3 hours. The obtained coagulated latex was filtered through a 325-mesh filter and dried in a fluidized bed dryer at 60°C for 6 hours to obtain an ABS high-glue powder with a moisture content of <1%. The ABS high-glue powders prepared in Examples 11-20, Comparative Examples 4-6, and Examples 21-22 were respectively recorded as ABS high-glue powder 1, ABS high-glue powder 2, ABS high-glue powder 3, ABS high-glue powder 4, ABS high-glue powder 5, ABS high-glue powder 6, ABS high-glue powder 7, ABS high-glue powder 8, ABS high-glue powder 9, ABS high-glue powder 10, ABS high-glue powder 11, ABS high-glue powder 12, ABS high-glue powder 13, ABS high-glue powder 14, and ABS high-glue powder 15.

[0054] Preparation method of ABS resin: According to Table 4-6, the components are mixed, extruded through a twin-screw extruder, cooled, and pelletized to obtain the ABS resin, wherein the extrusion temperature is 185-220°C, the screw speed is 300r / min, and the screw aspect ratio is 25:1.

[0055] ABS resin performance test:

[0056] (1) ABS surface pitting test: ABS resin was injection molded into a standard square plate (100 mm*100 mm*2 mm). The pitting on the square plate was counted using a Leica optical microscope (model DM6 M LIBS). Three samples were tested for each sample and the average number of pitting was calculated. The pitting was graded into 5A (0), 4A (1-2), 3A (3-5), 2A (6-10), and 1A (more than 10).

[0057] (2) Coating adhesion: The coating adhesion was tested according to ASTM B533(85)-2013 Peel strength of alloy-plated plastics. Five samples were tested for each sample and the average adhesion was calculated.

[0058] (3) Standard deviation of grafting rate: After drying, weigh about 1.000g of ABS high-glue powder, recorded as m0; weigh the weight of the reagent bottle, recorded as m1; put the high-glue powder into the reagent bottle and add about 25ml of acetone; shake for 2 hours to fully dissolve the high-glue powder; centrifuge in a high-speed centrifuge for 30 minutes, and set the centrifuge speed to 15,000 rpm; immediately remove the acetone solution after centrifugation, taking care not to bring out the powder at the bottom; add about 25ml of acetone and shake to fully mix the solution, and centrifuge again; remove the acetone solution after centrifugation; then put the bottle containing the insoluble matter into an oven at 80°C for 8 hours, and put it into a vacuum oven for further drying at 80°C for 4 hours, cool to room temperature, and weigh m2. Grafting rate = (m2-m1-m0*n) / (m0*n), where: m0: mass of ABS high-rubber powder, g; m1: weight of reagent bottle, g; m2: sum of mass of reagent bottle and separated material after drying, g; n: rubber content in ABS high-rubber powder, which is the feed ratio of dry basis of butadiene latex in Table 3 (weight of polybutadiene latex / (weight of polybutadiene latex+weight of styrene+weight of acrylonitrile)). Calculation method of grafting rate standard deviation: sample the same ABS high-rubber powder sample 10 times to test the grafting rate. First, subtract the average value of 10 tests from each test value to obtain a set of 10 data; secondly, add up the squares of the 10 data obtained in the previous step; thirdly, divide the sum by 10, and finally square it to obtain the square root to obtain the standard deviation of the grafting rate. The smaller the standard deviation of the grafting rate, the more stable the grafting rate.

[0059] Table 1 Examples 1-10 Proportions (parts by weight)

[0060]

[0061]

[0062] Table 2 Comparative Examples 1-3 Proportions (parts by weight)

[0063]

[0064] Table 3 Proportions of Examples 11-22 and Comparative Examples 4-6 (parts by weight)

[0065]

[0066]

[0067]

[0068] Table 4 Proportions of Examples 23-34 (parts by weight)

[0069]

[0070]

[0071] Table 5 Proportions of Examples 35-36 (parts by weight)

[0072]

[0073] Table 6 Comparative Examples 7-9 Proportions (parts by weight)

[0074]

[0075]

[0076] It can be seen from Tables 4-6 that the average particle size and the half-peak width of the number average particle size distribution curve of the polybutadiene latex used are within the scope of the present invention, so that the ABS resin has a better electroplating surface appearance and coating bonding strength, thereby improving the electroplating yield.

Claims

1. A polybutadiene latex, characterized in that: The average particle size of the polybutadiene latex is 290-315 nm, and the half-peak width of the number average particle size distribution curve is 20-150 nm. The residual butadiene monomer content in the polybutadiene latex accounts for 0.005%-1.6% of the dry basis of the entire polybutadiene latex.

2. The polybutadiene latex according to claim 1, characterized in that The average particle size of the polybutadiene latex is 300-310nm, and the half-peak width of the number average particle size distribution curve is 30-100nm; the residual butadiene monomer content in the polybutadiene latex accounts for 0.01%-0.8% of the dry basis of the entire polybutadiene latex.

3. The polybutadiene latex according to claim 1, characterized in that The weight fraction of the polybutadiene latex gel is 50-95%.

4. A method for preparing a polybutadiene latex as claimed in any one of claims 1 to 3, comprising: The raw materials are mixed and polymerized to obtain polybutadiene latex, wherein the raw materials are calculated by weight as follows: 95-115 parts of butadiene, 0.02-6 parts of initiator, 0.02-10 parts of electrolyte, 0.1-12 parts of emulsifier, 0.01-6 parts of chain transfer agent, 0.02-8 parts of rubber particle size controller, 0-6 parts of gel content regulator, 40-400 parts of water, and the rubber particle size controller is polyoxyethylene carboxylate.

5. The preparation method according to claim 4, characterized in that: The initiator includes one or more of sodium persulfate, potassium persulfate, ammonium persulfate, and azobisisobutylnitrile; the electrolyte includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate, and potassium hydroxide; and the emulsifier includes one or more of naphthalenesulfonic acid formaldehyde condensate sodium salt, naphthalenesulfonic acid formaldehyde condensate potassium salt, potassium oleate, potassium stearate, potassium disproportionated rosin acid, sodium dodecylbenzene sulfonate, and sodium dodecyl sulfonate.

6. The preparation method according to claim 4, characterized in that: The chain transfer agent includes one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, tetradecyl mercaptan, tridecyl mercaptan, undecyl mercaptan, and decanyl mercaptan; the rubber particle size control agent has a structural formula of RCOO (CH2CH2O) m H, wherein R is a long-chain alkyl group, the number of carbon atoms in the long-chain alkyl group is 4-19, and m is 4-11; the gel content regulator is a dialkyl dithioxanthate, wherein the number of carbon atoms in the alkyl group is 1-13.

7. The preparation method according to claim 4, characterized in that: The raw materials are calculated by weight as follows: 98-110 parts by weight of butadiene, 0.12-5 parts by weight of initiator, 0.05-6 parts by weight of electrolyte, 1-8 parts by weight of emulsifier, 0.1-4 parts by weight of chain transfer agent, 0.05-5 parts by weight of rubber particle size controller, 0.2-5 parts by weight of gel content regulator and 50-300 parts by weight of water.

8. The preparation method according to claim 4, characterized in that: The polymerization reaction is as follows: heating to 55-85° C. and reacting for 23-38 hours.

9. An ABS high-rubber powder, characterized in that: The ABS high-rubber powder is: a copolymer of polybutadiene latex, styrene and acrylonitrile as described in any one of claims 1 to 3.

10. The ABS high-rubber powder according to claim 9, characterized in that: The weight fraction of the polybutadiene latex is 50-70%, and the weight fraction of acrylonitrile is 4-20%.

11. An ABS resin, characterized in that: The ABS resin component comprises, by weight: 15-40 parts of the ABS high-rubber powder according to claim 9 and 60-78 parts of styrene-acrylonitrile copolymer.

12. A method for preparing the ABS resin according to claim 11, comprising: The components are mixed, extruded through a twin-screw extruder, cooled, and pelletized to obtain ABS resin.

13. Use of the ABS resin as claimed in claim 11 in electroplating parts for interior and exterior decoration of automobiles.